Bimolecular porous supramolecular networks deposited from solution on layered materials: graphite, boron nitride and molybdenum disulphide - Korolkov, Vladimir V.; Svatek, Simon A.; Allen, Stephanie; Roberts, Clive J.; Tendler, Saul J.B.; Taniguchi, Takashi; Watanabe, Kenji; Champness, Neil R.; Beton, Peter H. (Royal Society of Chemistry, 2014)
A two-dimensional porous network formed from perylene tetracarboxylic diimide (PTCDI) and melamine may be deposited from solution on the surfaces of highly oriented pyrolytic graphite (HOPG), hexagonal boron nitride (hBN) and molybdenum disulphide (MoS2). Images acquired using high resolution atomic force microscopy (AFM) operating under ambient conditions have revealed that the network forms extended orderedmonolayers (41 lm2) on HOPG and hBN whereas on MoS2 much smaller islands are observed.